Examining stigmatization towards pedophilia among university students / Amy Azrin Natasha Nizamdin, Mohd Nazir Rabun and Nurul Nazera Abdul Halem - Nizamdin, Amy Azrin Natasha; Rabun, Mohd Nazir; Abdul Halem, Nurul Nazera (Universiti Teknologi MARA, Kedah, 2019)
Stigmatization restricts people's opportunities in life and has severe consequences on mental health and psychological well-being. Level of stigmatization towards pedophilia is a concerned issue in the society as there are several high-profile cases highlighted have brought much attention for the past years. The present study examines on stigmatization level towards pedophilia among university students. In addition to that, it also tries to examine the relationship between parenting attachment, mental disorder, emergent of the internet and their stigmatization level towards pedophilia. A crosssectional survey among university students was employed for the purpose of this study. A quantitative method was used in this research and out of 400 questionnaires distributed only 370 were useable. Results found that majority of the students in UKM showed moderately high level of stigmatization towards pedophilia. The findings depicted that parenting attachment, mental disorder, and emergent of internet were significantly associated with the level of stigmatization towards pedophilia. Thus, this study contributes a greater understanding of pedophilia especially for university students as they have received proper education that will influence others’ perception on pedophilia. It is crucial for the university’s management to formulate effective campaigns and social work programmes to raise awareness on pedophilia issue.